Inclusive Education in Higher Educational Institutions of Uzbekistan: Legal Framework, Practice, and Prospects - Porsayeva, Malika (The Lingua Spectrum, 2025)
Amid the ongoing reform of the education system in the Republic of Uzbekistan, particular emphasis is placed on ensuring equal access to quality education for all categories of citizens. One of the key priorities in this area is the development of inclusive education, especially within the context of higher education. This article provides a detailed analysis of the institutional, legal, and organizational prerequisites for the advancement of inclusion following Uzbekistan’s ratification of the UN Convention on the Rights of Persons with Disabilities in 2021. It examines national programs and governmental measures aimed at integrating persons with disabilities into the education system. Statistical data are presented to illustrate the dynamics of recent changes, along with international experiences that highlight the relevance of creating an inclusive educational environment. Special attention is given to the issue of the psychosocial well-being of students with disabilities and the urgent need for training professionals capable of effectively working in inclusive learning settings.